Book loan delinquency in the University of the Philippines Libraries (Diliman) its causes and extent - Matulac, Luzviminda J. (1996)
The main objective of this study is to determine the causes and extent of book loan delinquency in the University of the Philippines (Diliman) libraries, school year 1994-1995. Specifically, the study sought to answer the following questions: 1) what are the factors/causes contributing to book loan delinquency among UP Diliman libraries' clients? 2) what are the subject fields of books mostly affected by book loan delinquency? 3) how many percent of the total number of books borrowed are unreturned for the second semester, 1994-1995n 4) how many percent of the total number of registered borrowers are delinquent users for second semester, 1994-1995n 5) what are the existing control measures to minimize book loan delinquency? 6) what are other measures or procedures to minimize if not to prevent book loan delinquency?